GAMBARAN KECEMASAN PERAWAT DALAM MENANGANI PASIEN HEMODIALISIS DI MASA PANDEMI COVID-19 TAHUN 2020 - Sri Lestari, Yustina; Melati, Nimsi; Tinambunan, Janetta Chien; Daniel, Novarini; Sudari, Ni Wayan (Jurnal Kesehatan, 2021)
Anxiety is an uneasy feeling due to discomfort or fear accompanied by a response. Nurses are people who deal directly with hemodialysis patients who are vulnerable groups during the COVID-19 pandemic. This study is aimed to know the description of nurses' anxiety in handling hemodialysis patients during the COVID-19 pandemic at 2020. The metodologi applied in this research were quantitative descriptive design through online survey methods. Data collection techniques used a questionnaire from the Zung-Self-Rating Anxiety Scale. The study used non-probability sampling techniques with accidental sampling with a number of respondents 62 hemodialysis nurses. Nurses who did not experience anxiety are 60 respondents (96,8%), and 2 (3,2%) others exsperienced mild to moderate anxiety. Based on the analysis we can conclude that for abaout 60 respondents did not experience anxiety and 2 others experineced mild to moderate anxiety. Suggestions: Conducted research using other methods namely qualitative methods with in-depth interview techniques